LIfe after tragedy : essays on faith and the First World War evoked by Geoffrey Studdert Kennedy - Brierley, Michael W., 1973-; Byrne, Georgina; Studdert-Kennedy, Andrew G. (The Lutterworth Press, 2018)
A collection of essays exploring the theological issues raised by the First World War, inspired by the noted wartime chaplain Geoffrey Studdert Kennedy.